PENGUATAN METODE PENGAJARAN KEPADA GURU-GURU SMA/SMK SEDERAJAT SE-KOTA PEKANBARU DALAM RANGKA MITIGASI BENCANA PANDEMI COVID-19 - Sugeng Purwantoro; Memen Akbar; Ardianto Wibowo (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Natural disasters or Force Majeur always have a tremendous impact on the education process, especially in carrying out the teaching and learning process in schools. The Covid-19 pandemic is one of the disaster factors in Riau Province which also has a tremendous impact on Indonesian education, especially in achieving learning and teaching targets. The Community Service Program was conducted on 8–9 July 2020 providing strengthening and encouraging training to 150-250 high school/vocational high school teachers from Riau Province and some from outside Riau Province. Training was provided on teaching methods and knowledge to anticipate delays in the teaching and learning process during the Covid-19 pandemic, namely providing online learning technology solutions using Google Classroom and Google Meet tools. The enthusiasm of the teachers is very good with the feedback, namely 90.7% of teachers use Google Classroom and 81.4% of teachers use Google Meet as a means of Video Conference to students.